Assessment Of Trophic Status In Bali Strait - Umi Zakiyah; Endang Yuli Herawati; Kusriani Kusriani (Research Journal of Life Science, 2015)
The nutrient content in Banyuwangi coastal environment mostly caused by human activities along the coastal area of Bali strait especially in Banyuwangi surrounding areas. The change of organic element content in waters will directly affect plankton community structure and the aquatic trophic level. The aimed of this research were to analyze the plankton community structure, and to observe the quality of aquatic and determine Bali Strait especially Banyuwangi coastal area trophic level. This research was done in October 2015 at Banyuwangi coastal area. Methods used in this research was descriptive with seawater sampling for water quality analysis of several parameter such as nitrates (NO3), phosphates (PO4), TOM (Total Organic Matter) and Chlorophyll-a, meanwhile other parameters were, temperature, pH, Dissolved Oxygen dan salinity from three different depth of three different stations, coastal area of Bangsring, Tandjung Wangi and Muncar. The results for water quality parameters showed that Bangsring coastal area was the most  healthy waters compared to Bangsring and Muncar. Meanwhile, there were tendency that the concentration mostly high in the surface and decrease along with the deeper depth. This condition presumed caused by the ARLINDO current that passed through Bali strait. Phytoplankton identified and calculated consisted of 3 division, namely Chlorophyta, Chrysophyta, and Cyanophyta with total density ranges between 4-2888 ind/ml. The value of diversity index phytoplankton (H’) ranges between 0,3-0,7. Based on the result it can be concluded that Banyuwangi coastal areas were at throphic level of  oligotrophic tended to mesotrophic in northern part and eutrophic especially in Muncar. Thus, it was suggested for the Government to prevent this area becoming more polluted in the future.